Industri Budaya dan Dramaturgi dalam Storytelling Iklan Instagram: Studi Kasus Konten @indrajegel - Panji Mukadis (MUKASI: Jurnal Ilmu Komunikasi, 2026)
Content from the @indrajegel Instagram account attracts audience attention through a storytelling style inspired by Chinese television melodrama. Chinese melodramatic content is commonly characterized by a degree of standardization, including distinctive and recurring background music. This melodramatic template has gained wider recognition through platforms such as ReelShort, which are supported by China’s “Going Global” cultural policy. Grounded in a constructivist perspective, this study examines the cultural industry phenomenon of influencer-based social media content through a case study of the @indrajegel account, focusing on why content that is consciously recognized as advertising can still capture audience attention by analyzing its dramaturgical aspects. This study offers novelty not only through its case selection, but also by addressing the limited number of studies that explicitly connect Chinese-style melodramatic content with cultural industry theory, particularly in relation to dramaturgical analysis. The findings demonstrate how the frontstage and backstage dimensions of the content generate a form of permission marketing through an entertaining three-act dramatic structure, resulting in high levels of audience engagement. These findings provide managerial implications for brands and influencers by highlighting the potential for exploring similar activation strategies inspired by the @indrajegel phenomenon. Future research may examine the advertising effectiveness of the same account, ranging from ad recall to purchase intention or actual purchasing behavior, as well as explore other influencer accounts with different content characteristics and creator backgrounds.